"It's so fluid, it's developing all the time": pre-service teachers' perceptions and understanding of cyberbullying in the school environment. Issue 5 (2nd September 2020) - Macaulay, Peter J. R.; Betts, Lucy R.; Stiller, James; Kellezi, Blerina
ABSTRACT: To gain an insight into how those entering the teaching profession regard cyberbullying, two focus groups were conducted with nine pre-service teachers (PSTs). Thematic analytical approach revealed three themes: (a) evolving nature of bullying, (b) involvement in cyberbullying and (c) management of cyberbullying. PSTs discussed how cyberbullying was evolving and becoming socially acceptable in the modern world. Participants addressed features of victimisation and perpetration associated with cyberbullying. PSTs reflected on the responsibility to address cyberbullying, discussing effective strategies to manage the issue. Participants considered the extent to which their initial teacher training course prepared prospective teachers to manage cyberbullying. Abbreviations: PSTs: Pre-service teachers; ITT: initial teacher training; ODE: online disinhibition effect